TUBUH, ILMU SOSIAL DAN RUANG PUBLIK MASYARAKAT MUSLIM - Yasir Alimi, Moh (Forum Ilmu Sosial, 2011)
Body provides the contexts as well as the outcomes of social changes in the public sphere of Muslim societies. However, bodies are not conceptually developed enough in the context of Indonesian social sciences. This article aims at outlining theoretical explorations of body in social theory, useful to understand the contemporary development in Islamic public sphere as well as the shift in political Islam. Drawing from a micro-study on the Islamic public sphere in Turkey and my own ethnographic work in South Sulawesi, I argue that Islamic public sphere can be approached conceptually and materially by analyzing bodies as its object of analysis. Analysing the body in the public sphere allows us to understand the current trend for Islamic visibilities and also strategy, particularly that of woman, to challenge the public sphere through their bodies. Key words: body, social theory, Islam, public space